2004
DOI: 10.1074/jbc.m405479200
|View full text |Cite
|
Sign up to set email alerts
|

The Human TAZ Gene Complements Mitochondrial Dysfunction in the Yeast taz1Δ Mutant

Abstract: Barth syndrome is a genetic disorder that is caused by different mutations in the TAZ gene G4.5. The yeast gene TAZ1 is highly homologous to human TAZ, and the taz1⌬ mutant has phospholipid defects similar to those observed in Barth syndrome cells, including aberrant cardiolipin species and decreased cardiolipin levels. Subcellular fractionation studies revealed that Taz1p is localized exclusively in mitochondria, which supports the theory that tafazzins are involved in cardiolipin remodeling. Because cardioli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 27 publications
9
88
0
Order By: Relevance
“…This was confirmed in our study because we observed growth defects of taz1⌬ cells on a nonfermentable carbon source and a reduction of mitochondrial inner membrane potential. These results agree well with previous studies, which reported that the function of the respiratory chain was compromised in taz1⌬ cells (Vaz et al, 2003;Gu et al, 2004;Ma et al, 2004). To determine how inactivation of the mitochondrial outer membrane protein Taz1 affected the respiratory chain, we visualized the respiratory chain protein complexes solubilized in the mild detergent digitonin by BN-PAGE (Cruciat et al, 2000;Schägger and Pfeiffer, 2000;Schägger et al, 2004).…”
Section: Taz1 and Respiratory Chain Complexessupporting
confidence: 90%
See 3 more Smart Citations
“…This was confirmed in our study because we observed growth defects of taz1⌬ cells on a nonfermentable carbon source and a reduction of mitochondrial inner membrane potential. These results agree well with previous studies, which reported that the function of the respiratory chain was compromised in taz1⌬ cells (Vaz et al, 2003;Gu et al, 2004;Ma et al, 2004). To determine how inactivation of the mitochondrial outer membrane protein Taz1 affected the respiratory chain, we visualized the respiratory chain protein complexes solubilized in the mild detergent digitonin by BN-PAGE (Cruciat et al, 2000;Schägger and Pfeiffer, 2000;Schägger et al, 2004).…”
Section: Taz1 and Respiratory Chain Complexessupporting
confidence: 90%
“…These analyses and recent studies (Ma et al, 2004) indicate a defect in respiratory chain function in taz1⌬ cells. In the light of the surprising outer membrane localization of Taz1 we wondered how defects in Taz1 would translate to a reduction of respiratory chain function at the inner membrane.…”
Section: Effect Of Taz1 Deletion On Inner Membrane Protein Complexessupporting
confidence: 74%
See 2 more Smart Citations
“…Specific involvement of CL corresponded with the mitochondrial localization of tafazzin. 28 However, the lipid abnormalities in BTHS were not confined to CL. PC showed a distinct alteration of its fatty acid composition, which, although less drastic than in CL, was consistently present in lymphoblasts from BTHS patients.…”
Section: Discussionmentioning
confidence: 97%